Childrearing and the shaping of children’s emotional experiences and expressions in two Argentinian communities - Remorini, Carolina (2012)
This article analyzes the role of children’s social environment in shaping children’s emotional expressions. It is based on the findings of an ongoing research study interrogating childrearing practices in two rural populations representing two contrasting ecological contexts in Argentina: Mbya Guarani indigenous communities located in the northeast rainforest (Misiones Province) and creole communities from Molinos (Salta Province), in the highlands and semiarid areas of Argentinean northwest. The focus of this article is on the ways in which adults interpret and respond to children’s crying as one manifestation of emotional behavior. This article attempts a comparative analysis of representations, attitudes and behaviors regarding children’s crying. It is stressed how discourses of childhood validate some expressions of emotion and restrict and pathologize others. On one hand, parents from both populations not only differ in their tolerance of children’s crying but also differ in their evaluation of the difficulties of rearing ‘weeping’ children. On the other hand, in both populations excessive senseless crying represents a risk for children’s health as it is considered a symptom of several illnesses. Based on these considerations, at the end of this article each population’s ethnotheories of children’s appropriate emotional behavior is analyzed, and the implications of these ethnotheories for emotion socialization.